Expanded circulating follicular dendritic cells facilitate immune responses in chronic HBV infection - Xiaoyi Li; Qifan Zhang; Wanyue Zhang; Guofu Ye; Yanchen Ma; Chunhua Wen; Shuqin Gu; Libo Tang; Yongyin Li (Journal of Translational Medicine, 2020)
Abstract Background The restoration of host hepatitis B virus (HBV)-specific antiviral immunity is an effective strategy for hepatitis B recovery. Follicular dendritic cells (FDCs) play a crucial role in immune regulation. The goal of the present study was to investigate the characteristics and functions of FDCs in chronic HBV infection. Methods The frequencies of FDCs in peripheral blood, liver, and spleen were measured in patients with chronic HBV infection. Isolated FDCs from splenic tissues of HBV-related liver cirrhosis-induced hypersplenism patients were cultured with autologous intrasplenic CD4+ T cells and CD19+ B cells. Results We observed that patients with chronic HBV infection had a significantly increased frequency of circulating FDCs compared to that of healthy controls. Additionally, the frequency of circulating FDCs was positively correlated with that of intrahepatic and intrasplenic counterparts. Moreover, positive correlations were observed between the frequencies of circulating FDCs and plasmablast and memory B cells, as well as C-X-C motif chemokine receptor type 5 (CXCR5)+CD4+ T cells and CXCR5+CD8+ T cells. Notably, in vitro experimental results demonstrated that FDCs derived from splenic tissues of chronic HBV patients facilitated interferon-γ and interleukin-21 production from autologous intrasplenic CD4+ T cells and promoted the proliferation of autologous intrasplenic CD19+ B cells. Conclusions Expanded FDCs in patients with chronic HBV infection may favor host immune responses against HBV. The identification of this unique population of cell may contribute to a better understanding of the immune regulatory mechanisms associated with chronic HBV infection and provide a potential immunotherapeutic target for this disease.